Impact of Group Discussion on Japanese Listening Skills for Oral Comprehension Subject Through Zoom - Robihim Robihim; Irawati Agustine (STAI Hubbulwathan Duri, 2022)
The purpose of the study was to determine the impact of implementing group discussions on improving Japanese listening skills in oral comprehension courses. This research is experimental research with Quasy Experimental method with Posttest only control group design. The sampling technique used was the non-probability sampling technique. So, the research sample consisted of 2 classes of 60 students. The data collection techniques used were observation and listening tests. Data analysis used a t-test to determine listening skills before and after using group discussions. The results showed that the value of t-Statt-Table (-13,863 2,0009), meaning that group discussions conducted through zoom positively impacted listening skills. Meanwhile, the level of oral understanding found from the listening test components shows a weakness in the evaluation component of the statements given from the information discussed. The ability to understand the questions in dialogue that are practised in group discussions becomes a very good component of oral comprehension. So, the results of this study have implications for the teacher's understanding that discussions improve students' speaking skills and can also affect the level of listening skills.